PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PRESTASI BELAJAR SISWA KELAS VIII SMP NEGERI 40 PEKANBARU - Salsabilla Ramadhona; Jumili Arianto; Haryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the learning achievement of class VIII students of SMP Negeri 40 Pekanbaru in the Pendidikan Pancasila subject. The background of this study is based on the low activity and learning achievement of students caused by the use of conventional learning methods that tend to be one-way and less actively involve students. This study uses a quantitative approach with an experimental method and a Pretest-Posttest Control Group Design. The research sample consisted of two classes, namely the experimental class which was given treatment using the PBL model and the control class which used the lecture method. The instruments used were pretest and posttest tests and observations. The results showed that the average posttest score of the experimental class was 74, while the control class was 65.67. The t-test showed tcount (2.476) > ttable (1.671) which means there is a significant difference between the two groups. In addition, the N-Gain value of the experimental class was 0.3956 (moderate category), while the control class was 0.2016 (low category). Thus, it can be concluded that the Problem Based Learning learning model has a positive effect on improving student learning achievement. This model is also able to create more active, collaborative, and contextual learning in accordance with the demands of the Merdeka Curriculum.